Some legal implications of web linking - Roudi, Anuschka (Centre for Law and Society, 2026)
The explosive expansion of the Internet during the recent years has provoked many lawsuits that left lawyers struggling with the application of traditional, "analogue" law to the new, digital technology. Yet, another pattern of disputes emerges that involves unauthorised Web linking in various forms. Technology meanwhile provides for the possibility to either incorporate images originating from another source on the Web into the own Web site or to frame content from other providers into the own material published on the Web simply by using hypertext links. These activities, along with more traditional kinds of links, have lead to disputes between content providers on the Internet about linking in general and specific kinds of links in particular. Four celebrated linking disputes, one in the Great Britain and three in the United States, gained interest in the cyber world because of their potential impact on the main feature of the Web, the possibility of linking documents. Thus far, only one court decision was issued in the Scotland, the other lawsuits were either settled or they are still pending. Notwithstanding. this uncertainty in law, similar situations have evolved and the demand for a solution is growing. Commentators around the world have tried to deal with the issue and it appears that in many jurisdictions traditional intellectual property law is difficult to apply to the new technology.